93O First results of phase I/II studies evaluating viral vector-based heterologous prime/boost immunotherapy against predicted HLA class I neoantigens demonstrate CD8 T cell responses in patients with advanced cancers. (15th December 2019) - Johnson, M L; Spira, A; Carbone, D P; Drake, C; Henick, B; Ingham, M; Caldwell, K; Chan, S; Hart, M; Malloy, A; Maloney, E; Palmer, C; et al.
Abstract: Background: Genetically engineered viruses induce strong T-cell responses against infectious pathogens in humans. Virus-based vectors expressing non-self tumor antigens are an attractive option to induce strong tumor-specific T cells. Methods: Two ongoing phase I/II trials, GO-004 and GO-005, deploy an heterologous prime/boost immunotherapy to target neoantigens in combination with immune checkpoint blockade. The prime is a modified chimpanzee adenovirus. Boosts use a self-amplifying mRNA formulated in lipid nanoparticles. Both prime and boosts express the same 20 neoantigens. In GO-004, patient-specific neoantigens are predicted using a proprietary machine learning-based HLA Class I prediction model (EDGE) and incorporated into a patient-specific immunotherapy. GO-005 uses an off-the-shelf immunotherapy expressing shared neoantigens administered to patients with a matching tumor mutation and HLA Class I allele for antigen presentation. Results: To date, 5 patients with advanced gastroesophageal adenocarcinoma, lung and colorectal (MSS) cancers have been treated in combination with nivolumab in both studies. No DLTs have been observed and treatment-related adverse events include reversible Grade 1/2 injection site reactions (3/5), fever (3/5, including 1 patient with 2 transient Grade 2 SAEs), skin rash (1/5), dermatitis (1/5), and asymptomatic Grade 3 CK elevation (1/5). In the first 3 patients analyzed to date in GO-004, overnight IFNg ELISpot assays revealed neoantigen-specific CD8 T-cell responses 2-4 weeks after priming that were further enhanced with subsequent boosts to levels >500 spots/10 6 PBMCs. Broad polyfunctional CD8 T-cell responses to multiple neoantigens were observed including de novo priming of T cells. Conclusion: Patients treated with a heterologous viral vector-based immunotherapy produce remarkable CD8 T-cell responses specific for predicted HLA Class I neoantigens. These results demonstrate proof-of-concept for the immunogenicity of our novel prime/boost approach. Treatment was well tolerated without DLTs. Additional patients and data will be presented. Clinical trial identification: NCT03639714; NCT03953235. Legal entity responsible for the study: Gritstone Oncology. Funding: Gritstone Oncology. Disclosure: M.L. Johnson: Research grant / Funding (institution), Travel / Accommodation / Expenses: Genentech/Roche; Research grant / Funding (institution), Travel / Accommodation / Expenses: Boehringer Ingelheim; Research grant / Funding (institution), Travel / Accommodation / Expenses: AstraZeneca; Research grant / Funding (institution), Travel / Accommodation / Expenses: Merck; Research grant / Funding (institution), Travel / Accommodation / Expenses: Incyte; Research grant / Funding (institution), Travel / Accommodation / Expenses: Pfizer; Research grant / Funding (institution): Guardant Health; Research grant / Funding (institution), Travel / Accommodation / Expenses: Bristol-Myers Squibb; Research grant / Funding (institution): Oncomed; Research grant / Funding (institution): BerGenBio; Research grant / Funding (institution): Lilly; Travel / Accommodation / Expenses: Sysmex; Travel / Accommodation / Expenses: Vapotherm; Research grant / Funding (institution), Travel / Accommodation / Expenses: EMD Serono; Research grant / Funding (institution), Travel / Accommodation / Expenses: Daiichi Sankyo; Travel / Accommodation / Expenses: Exelixis; Research grant / Funding (institution), Travel / Accommodation / Expenses: AbbVie; Research grant / Funding (institution), Travel / Accommodation / Expenses: Gritstone Oncology; Research grant / Funding (institution): Genocea; Research grant / Funding (institution): Sanofi; Research grant / Funding (institution): Kadmon; Research grant / Funding (institution): Janssen; Research grant / Funding (institution): Mirati; Research grant / Funding (institution): Genmab; Research grant / Funding (institution): StemCentRx; Research grant / Funding (institution): Novarits; Research grant / Funding (institution): Checkpoint Therapeutics; Research grant / Funding (institution): Array BioPharma; Research grant / Funding (institution): Regeneron; Research grant / Funding (institution): Hengrui Pharmaceutical; Research grant / Funding (institution): Lycera; Research grant / Funding (institution): BeiGene; Research grant / Funding (institution): Tarveda Therapeutics; Research grant / Funding (institution): Loxo; Research grant / Funding (institution): Foundation Medicine; Research grant / Funding (institution): Mersana; Research grant / Funding (institution): CytomX Therapeutics; Research grant / Funding (institution): Dynavax; Research grant / Funding (institution): Bridie; Research grant / Funding (institution): Corvus; Research grant / Funding (institution): Amgen; Research grant / Funding (institution): Adaptimmune; Research grant / Funding (institution): Syndax; Research grant / Funding (institution): G1 Therapeutics; Research grant / Funding (institution): Clovis; Research grant / Funding (institution): Acerta Pharma. A. Spira: Research grant / Funding (self), Research grant / Funding (institution): Gritstone Oncology. D.P. Carbone: Research grant / Funding (institution): Gritstone Oncology; Research grant / Funding (self), Research grant / Funding (institution): Bristol-Myers Squibb; Advisory / Consultancy: Abbvie; Advisory / Consultancy: Agenus; Advisory / Consultancy: Amgen; Advisory / Consultancy: Ariad; Advisory / Consultancy: AstraZeneca; Advisory / Consultancy: Biocept; Advisory / Consultancy: Boehringer Ingelheim; Advisory / Consultancy: Celgene; Advisory / Consultancy: Clovis; Advisory / Consultancy: EMD Serono; Advisory / Consultancy: Foundation Medicine; Advisory / Consultancy: Genentech/Roche; Advisory / Consultancy: Glaxo-Smith-Kline; Advisory / Consultancy: Guardant Health; Advisory / Consultancy: Helsinn; Advisory / Consultancy: Humana; Advisory / Consultancy: Incyte; Advisory / Consultancy: Inivata; Advisory / Consultancy: Inovio; Advisory / Consultancy: Janssen; Advisory / Consultancy: Kyowa Kirin; Advisory / Consultancy: Loxo Oncology; Advisory / Consultancy: Merck; Advisory / Consultancy: MSD; Advisory / Consultancy: Nexus Oncology; Advisory / Consultancy: Novartis Oncology; Advisory / Consultancy: Palobiofarma; Advisory / Consultancy: Pfizer; Advisory / Consultancy: prIME Oncology; Advisory / Consultancy: Stemcentrx; Advisory / Consultancy: Takeda Oncology; Advisory / Consultancy: Teva. C. Drake: Research grant / Funding (institution): Gritstone Oncology; Advisory / Consultancy, Research grant / Funding (self), Licensing / Royalties: Bristol-Myers Squibb; Advisory / Consultancy, Shareholder / Stockholder / Stock options: Compugen; Advisory / Consultancy, Shareholder / Stockholder / Stock options: Potenza; Advisory / Consultancy, Research grant / Funding (self), Licensing / Royalties: Janssen; Advisory / Consultancy: Merck; Advisory / Consultancy: Agenus; Advisory / Consultancy: Roche/Genentech; Advisory / Consultancy: Tizona Therapeutics; Shareholder / Stockholder / Stock options: Harpoon; Advisory / Consultancy, Shareholder / Stockholder / Stock options: Kleo; Advisory / Consultancy, Shareholder / Stockholder / Stock options: Werewolf; Advisory / Consultancy: Bayer; Advisory / Consultancy: Merck-Serono; Advisory / Consultancy: Pfizer; Advisory / Consultancy: Pierre Fabre; Advisory / Consultancy: Shattuck Labs. B. Henick: Advisory / Consultancy: Boehringer Ingelheim; Research grant / Funding (institution): Gritstone Oncology. M. Ingham: Research grant / Funding (institution): Gritstone Oncology. K. Caldwell: Shareholder / Stockholder / Stock options, Full / Part-time employment: Gritstone Oncology. S. Chan: Shareholder / Stockholder / Stock options, Full / Part-time employment: Gritstone Oncology. M. Hart: Shareholder / Stockholder / Stock options, Full / Part-time employment: Gritstone Oncology. A. Malloy: Shareholder / Stockholder / Stock options, Full / Part-time employment: Gritstone Oncology. E. Maloney: Shareholder / Stockholder / Stock options, Full / Part-time employment: Gritstone Oncology. C. Palmer: Shareholder / Stockholder / Stock options, Full / Part-time employment: Gritstone Oncology. A. Yang: Shareholder / Stockholder / Stock options, Full / Part-time employment: Gritstone Oncology. M. Zhong: Shareholder / Stockholder / Stock options, Full / Part-time employment: Gritstone Oncology. P. Basciano: Shareholder / Stockholder / Stock options, Full / Part-time employment: Bristol-Myers Squibb. E. Bournazou: Shareholder / Stockholder / Stock options, Full / Part-time employment: Bristol-Myers Squibb. A.R. Ferguson: Shareholder / Stockholder / Stock options, Full / Part-time employment: Gritstone Oncology. D. Catenacci: Honoraria (self), Research grant / Funding (institution): Gritstone Oncology; Honoraria (self): Merck; Honoraria (self): Bristol-Myers Squibb; Honoraria (self): Astellas; Honoraria (self): Lilly; Honoraria (self): Taiho; Honoraria (self): Five Prime; Speaker Bureau / Expert testimony: Guardant Health, Inc.; Speaker Bureau / Expert testimony: Foundation Medicine; Speaker Bureau / Expert testimony: Tempus; Honoraria (self): Roche/Genentech; Honoraria (self): Amgen.